A Technological Review of Direct Air Carbon Capture and Storage (DACCS): Global Standing and Potential Application in Australia - Domingo Garza; Paul Dargusch; David Wadley (Energies, 2023)
There is mounting evidence that, unless greenhouse gas (GHG) emissions fall back quickly, the goals outlined by the 2015 Paris Agreement to keep the global temperature rise well below 2 °C and preferably 1.5 °C will not be met. In response to these concerns, direct air carbon capture and storage (DACCS) technologies are gaining research and development attention. This article provides a thorough comparison of the two leading DACCS variants and reports on their status among major research and policy institutions worldwide. By translating the operating and capital costs to the Australian context, we assess the viability of DACCS implementation using either cheap renewable or legacy fossil energy to power CO2 extraction plants.